1988
DOI: 10.1128/mcb.8.3.1247
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor alpha: mutation of aspartic acid 47 and leucine 48 results in different biological activities.

Abstract: To study the relationship between the primary structure of transforming growth factor alpha (TGF-alpha) and some of its functional properties (competition with epidermal growth factor (EGF) for binding to the EGF receptor and induction of anchorage-independent growth), we introduced single amino acid mutations into the sequence for the fully processed, 50-amino-acid human TGF-alpha. The wild-type and mutant proteins were expressed in a vector by using a yeast alpha mating pheromone promoter. Mutations of two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…In either case, a careful structure-function analysis of TGF-a is needed to understand how to exploit the therapeutic potential of TGF-a. Prior studies from our laboratory (5) and others (13,14) have shown that nonconservative amino acid substitutions with alanines at positions His-12, Phe-15, Tyr-38, Arg-42, Asp-47, and Leu-48 decrease the receptorbinding and growth-promoting activities of TGF-a. By contrast, conservative amino acid substitutions at positions Lys-29 and Tyr-38 have little or no effect on the biological properties of TGF-a.…”
mentioning
confidence: 99%
“…In either case, a careful structure-function analysis of TGF-a is needed to understand how to exploit the therapeutic potential of TGF-a. Prior studies from our laboratory (5) and others (13,14) have shown that nonconservative amino acid substitutions with alanines at positions His-12, Phe-15, Tyr-38, Arg-42, Asp-47, and Leu-48 decrease the receptorbinding and growth-promoting activities of TGF-a. By contrast, conservative amino acid substitutions at positions Lys-29 and Tyr-38 have little or no effect on the biological properties of TGF-a.…”
mentioning
confidence: 99%
“…Mutants of Tyr-38 were further purified as described previously (18). The elution profiles on a Biogel P30 column for the mutant TGF-cx proteins were identical to that shown for wild-type TGF-a in a previous paper (18).…”
mentioning
confidence: 99%
“…The maximum activities in both radioreceptor and soft-agar assays were found in the same fraction, called the peak fraction. The activities were expressed in terms of EGF equivalence as reported previously (18). The peak fractions were also tested in thymidine incorporation assays and in radioimmunoassays (with the Biotope polyclonal antibody in denaturing conditions).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Also for TGF-␣ residues from both the N-terminal and the Cterminal loops are important for receptor binding. 38,39 The Cterminal fragment of H194T20 is derived from TGF-␣ and might be functional in a manner similar to the wild-type ligand. The N-terminal binding site of H194T20 is composed of both HRG-␤1 and TGF-␣ sequences.…”
Section: Discussionmentioning
confidence: 99%